1999
DOI: 10.1182/blood.v93.10.3338.410k05_3338_3346
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Mast Cell-Committed Progenitors Present in Human Umbilical Cord Blood

Abstract: Human mast cells are derived from CD34+ hematopoietic cells present in cord blood, bone marrow, and peripheral blood. However, little is known about the properties of the CD34+ cells. We demonstrated here that mast cell progenitors that have distinct phenotypes from other hematopoietic cell types are present in cord blood by culturing single, sorted CD34+ cells in 96-well plates or unsorted cells in methylcellulose. The CD34+ mast cell-committed progenitors often expressed CD38 and often lacked HLA-DR, whereas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(52 citation statements)
references
References 41 publications
2
50
0
Order By: Relevance
“…Early reports by use of in vitro MC-differentiation models revealed that these progenitors circulate as CD34 + /CD117 + agranular mononuclear cells [25], which express the CD133 (prominin 1) stem cell-associated marker [26], together with myeloid-associated antigens, such as CD13 (aminopeptidase N) [24] and CD33 (siglec-3) [26], in the absence of the CD14 (LPS receptor) monocytic marker, CD17 (lactosylceramide) [27], and Fc«RI [13,25]. In addition, these precursors have been frequently shown to express CD38 and often to lack HLA-DR expression [28]. More recent ex vivo studies, based on the analysis of BM samples from healthy individuals and MDS patients, identified MCPs on phenotypic grounds as a minor subpopulation of CD34 + HPC, showing a CD117 high HLA-DR 2/int profile, the frequency of such MCPs ranging from ,0.001% to 0.02% of the whole CD34+ HPC compartment (mean of ,0.001% 6 0.005% BM cells) [29].…”
Section: Mc-committed Precursor Cells and Normal MC Maturation Patternsmentioning
confidence: 99%
See 1 more Smart Citation
“…Early reports by use of in vitro MC-differentiation models revealed that these progenitors circulate as CD34 + /CD117 + agranular mononuclear cells [25], which express the CD133 (prominin 1) stem cell-associated marker [26], together with myeloid-associated antigens, such as CD13 (aminopeptidase N) [24] and CD33 (siglec-3) [26], in the absence of the CD14 (LPS receptor) monocytic marker, CD17 (lactosylceramide) [27], and Fc«RI [13,25]. In addition, these precursors have been frequently shown to express CD38 and often to lack HLA-DR expression [28]. More recent ex vivo studies, based on the analysis of BM samples from healthy individuals and MDS patients, identified MCPs on phenotypic grounds as a minor subpopulation of CD34 + HPC, showing a CD117 high HLA-DR 2/int profile, the frequency of such MCPs ranging from ,0.001% to 0.02% of the whole CD34+ HPC compartment (mean of ,0.001% 6 0.005% BM cells) [29].…”
Section: Mc-committed Precursor Cells and Normal MC Maturation Patternsmentioning
confidence: 99%
“…Despite this, relative consensus exists in the literature about the phenotypic pattern of expression of several molecules, during MC maturation. Accordingly, early MCPs are known to express a set of early hematopoietic (CD34, CD38, CD45, CD38, HLA-DR) and myeloid markers (CD13, CD33) [24,26,28], as well as multiple cytokine and chemokine receptors (CD116, CD117, CD123, CD126, CXCR1, CXCR2, CXCR4) [26,30,37] and adhesion molecules (CD29, CD49d, CD49e, CD11a, CD18, CD44, CD54, CD58; see Table 1) [26,30,38]. During MC maturation, expression of some of these molecules remains relatively unchanged (e.g., CD29, CD44, CD58, CXCR2, CXCR4) [26,37,38], or it is even up-regulated (e.g., CD117, CD13, CD45) [26], whereas other molecules show decreased expression levels (e.g., the adhesion-related molecules CD49d, CD49e, CD11a, and CD18) [38], or they even become undetected in more mature MCs (e.g., CD34, CD116, CD123, CD126; see Table 1) [30,37].…”
Section: Mc-committed Precursor Cells and Normal MC Maturation Patternsmentioning
confidence: 99%
“…Mast cells (MCs) are multi-functional tissue-dwelling cells involved in various pathological conditions such as allergy and asthma, and their contribution to cardiovascular diseases and rheumatoid arthritis has also been suggested [1][2][3][4]. MCs are filled with cytoplasmic secretory granules that contain preformed mediators including cytokines, heparin, histamine, and two neutral serine proteases: tryptase and chymase [5][6][7][8]. Mature MCs can be distinguished from other cells by their expression of high-affinity IgE receptor [Fc epsilon receptor I (FceRI)] and c-kit (CD117) on their surface, and tryptase and heparin in their granules [1,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Human mast cells were differentiated from cord blood‐derived progenitor cells . In brief, stem cells were isolated from heparinized human cord blood by gradient centrifugation and magnetic enrichment for CD133‐positive cells (CD133 Micro Bead kit; Miltenyi Biotech, #130‐050‐801, Bergisch Gladbach, Germany).…”
Section: Methodsmentioning
confidence: 54%